A massive transrectal herniation of terminal ileal loops as a complication of a recent STARR procedure - Montatore, Manuela; Muscatella, Gianmichele; Masino, Federica; Gifuni, Rossella; Carpentiere, Rossella; Fares Bucci, Andrea; Guglielmi, Giuseppe (Acta Biomedica Atenei Parmensis, 2024)
This case report describes the complications of a recent STARR procedure (Stapled Trans-Anal Rectal Resection), in a female patient with a rectal prolapse. The protrusion of the rectum through the anus is a defining feature of the disorder known as rectal prolapse. Rectal prolapse therapy frequently involves the STARR procedure, a minimally invasive surgical approach. Post-operative problems, however, can occur and require extra treatments. This case report discusses the radiological results after a CT and the following treatments of a patient, who had severe complications after a STARR surgery. Less than 48 hours after surgery, the patient arrives in the Radiology Department, totally non-cooperative to do a CT, due to the worsening clinical condition into a complete shock status. The radiological findings revealed a significant trans-rectal herniation of the terminal ileal loops, which was also visible from the outside, so the patient underwent an urgent surgical intervention to reposition the loops and repair the prolapsed segment, to avoid severe consequences. After the procedure, the patient’s symptoms decreased, and she was released after a long hospitalization with a favorable prognosis. To diagnose these complications and identify proper management methods that could prevent serious further consequences, up until the patient’s death, radiological imaging, such as CT with contrast medium, and corrective surgery is essential.